Development of Self Competence Towards Excellent Hr - Novita Wahyu Setyawati; Dewi Sri Woelandar; Murti Wijayanti; Pradhana Arief S (PT FORMOSA CENDEKIA GLOBAL, 2023)
The existing problems can be concluded that the existing problem is that there are still young people who do not know what potential lies within them and if faced with a problem they are still hesitant to find a solution. From the existing problems, the solution taken is to provide motivation for the potentials that exist within and provide knowledge about how to solve a problem. The output targets to be achieved in community service this time are aspects of competence, being able to find a picture of the potential that exists within him and increasing abilities and skills in solving problems, aspects of management, being able to carry out self-planning to face future challenges and aspects of academics , the results of the activity will be reported and published in one of the local national journals.